Innovative In Vitro-In Silico Platform for Dose–Response Modeling in Canine Bladder Cancer: A 3D Organoid- and Mathematics-Based Approach - Mackenzie Long; Yvonne Peng; Saumya Gade; Hannah Nicholson; Michael Catucci; Christopher Zdyrski; Aleksandra Pawlak; Megan Corbett; Corey Saba; Travis Laver; Emily Rawlings; Maria Orbay-Cerrato; et al. (The AAPS Journal, 2026)

Predictions of southern migration timing in coastal sharks under future ocean warming - Maria H. Manz; Oliver N. Shipley; Robert M. Cerrato; Robert E. Hueter; Alisa L. Newton; John P. Tyminski; Bryan R. Franks; Tobey H. Curtis; Christopher Fischer; Joshua P. Zacharias; Christopher Scott; Keith J. Dunton; et al. (Conservation Biology, 2025)
Projected redistribution of marine species due to ocean warming may undermine current conservation efforts. Yet, there have been few studies on how ocean warming may alter migration timing. Across 5 years of acoustic telemetry data (2018–2022), we determined environmental drivers of southward migration timing for 6 migratory shark species from summer habitats in the Northwest Atlantic Ocean. We then forecasted how migratory timing from 3 regions, between the New England shelf and Mid‐Atlantic Bight, would respond under future sea surface temperatures (SSTs). Photoperiod and SST were strong predictors of southern migration in sharks, but the strength of these effects varied latitudinally. Overall, we found delayed departure dates from summer habitats under future elevated SSTs, indicating prolonged residency in northern habitats (median = ∼12 days). Sandbar sharks ( Carcharhinus plumbeus ) exhibited the largest delay in the onset of southern migrations (median = 29 days), whereas sand tiger sharks ( Carcharias taurus ) and white sharks ( Carcharodon carcharias ) exhibited the smallest delay (median = 1 day). Delays in migration timing of coastal shark species may alter local ecosystem dynamics and challenge current management strategies. These findings illustrate the utility of collaborative data‐sharing networks to expand understanding of broadscale animal movements and contribute to effective species management under a changing climate.

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Response to Seawater Exposure During the Flowering Stage of Two Dune-Building Grasses: Calamagrostis arenaria (L.) Roth and Thinopyrum junceum (L.) Á.Löve - M. D. Cerrato; A. Ribas-Serra; P. M. Mir-Rosselló; I. Cortés-Fernández; C. Douthe; C. Cardona; A. Sureda; J. Flexas; L. Gil (Journal of Plant Growth Regulation, 2024)
Human disturbance and seawater intrusion have unpredictable effects on coastal species. Dune systems are crucial coastal habitats because they provide natural front protection against seawater influence. Adult plant stands in dunes are important since they maintain dune structure. This study evaluated salinity stress responses in adult plants of two key dune-building grasses differing in salt tolerance: Thinopyrum junceum (tolerant) and Calamagrostis arenaria (less tolerant). Cultivated plants were exposed to various seawater (SW) dilutions (Tap-Water, 6.25%, 12.5%, 25%, 50%, and 100%) and gas exchange measurements and oxidative stress biomarkers were determined after two months of treatment. Stress conditions were maintained until flowering to assess effects on the reproductive effort. The reproductive response showed high plasticity at various inflorescence stages in T. junceum , minimizing abortion processes. C. arenaria showed lower plasticity and higher abortion rates. Physiological traits responded similarly to salinity in both species, with greater effect on F v / F m decrease and non-photochemical quenching increase for T. junceum . Biochemical patterns of response were also similar, with increasing enzymatic activities at 25% SW treatment, mainly for glutathione reductase and peroxidase (GSH and GPx), and stress damage occurring at 50% and 100% SW treatments for increased malonaldehyde (MDA) levels. These findings provide insight into the salinity tolerance mechanisms of dune-building grasses. Higher salinity tolerance is suggested for T. junceum based on better reproductive effort. Higher juvenile tolerance, faster growth, and plant cycle adjustments are indicated as key traits for higher salinity tolerance of T. junceum in contrast to C. arenaria .

Time pattern variation of alien plant introductions in an insular biodiversity hotspot: the Balearic Islands as a case study for the Mediterranean region - M. D. Cerrato; I. Cortés-Fernández; A. Ribas-Serra; P. M. Mir-Rosselló; C. Cardona; L. Gil (Biodiversity and Conservation, 2023)
Allochthonous plant species are considered among the main environmental issues worldwide, being especially accused in the Mediterranean basin. The present study aims to update Balearic Alien Flora and discuss its time and spatial variation and invasiveness. Information regarding allochthonous plant records of the Balearic Islands were gathered and analysed based on published checklists and online databases. For each species several general traits were assigned based on previous references to characterise the alien Balearic Flora. Records of allochthonous species between 1827 and 2023 indicate that Alien Balearic Flora is composed of 624 taxa recorded unevenly among islands, with lower records in smaller islands. Alien flora is mainly composed of therophytes and phanerophytes being held mainly in human related habitats. Introduction pathway is mainly ornamental, with over 50% of taxa entering through gardening and horticultural practices. Main biogeographical origins are American, Mediterranean, Euroasiatic and Cape origins. Invasive status of Balearic alien flora shows that 44% of all taxa can be regarded as casual, while 35% are naturalised, and 17% can be considered invasive, being the latter increased in smaller islands. Time variations trends starting mainly in the 70 s and predictive models show that alien species increase exponentially, being the most represented taxa from synanthropic habitats, introduced as ornamentals, lianas, phanerophytes and therophytes from Cactaceae , Asteraceae and Leguminosae families. The results of the present study can serve as a model to facilitate the scientifically informed decision making and management of plant invasions both in the Balearic Islands and other continental insular systems and Mediterranean regions.

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Evidence for Ecosystem Changes Within a Temperate Lagoon Following a Hurricane-Induced Barrier Island Breach - Jill A. Olin; Robert M. Cerrato; Janet A. Nye; Skyler R. Sagarese; Matthew Sclafani; Joshua P. Zacharias; Michael G. Frisk (Estuaries and Coasts, 2020)

Economic assessment of fidaxomicin for the treatment of Clostridium difficile infection (CDI) in special populations (patients with cancer, concomitant antibiotic treatment or renal impairment) in Spain - C. Rubio-Terrés; J. Cobo Reinoso; S. Grau Cerrato; J. Mensa Pueyo; M. Salavert Lletí; A. Toledo; P. Anguita; D. Rubio-Rodríguez; M. Watt; R. Gani (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Dispersal and connectivity effects at different altitudes in the Euphydryas aurinia complex - L. P. Casacci; C. Cerrato; F. Barbero; L. Bosso; S. Ghidotti; M. Paveto; M. Pesce; E. Plazio; G. Panizza; E. Balletto; R. Viterbi; S. Bonelli (Journal of Insect Conservation, 2015)

Instability of an aromatic amine in fatty food and fatty food simulant: characterisation of reaction products and prediction of their toxicity - R. Paseiro-Cerrato; A. Rodríguez-Bernaldo de Quirós; R. Sendón; J. Bustos; J.J. Sánchez; J. López-Hernández; P. Paseiro-Losada (Food Additives & Contaminants: Part A, 2015)

Rapid multi-analyte quantification of benzophenone, 4-methylbenzophenone and related derivatives from paperboard food packaging - R. Koivikko; S. Pastorelli; A. Rodríguez-Bernaldo de Quirós; R. Paseiro-Cerrato; P. Paseiro-Losada; C. Simoneau (Food Additives & Contaminants: Part A, 2010)

Spleen size variations and reproduction in a Mediterranean population of wild boar ( Sus scrofa ) - P. Fernndez-Llario; A. Parra; R. Cerrato; J. Hermoso de Mendoza (European Journal of Wildlife Research, 2004)